Usaha Meningkatkan Produksi Daging Ternak Domba dan Kambing Melalui Peningkatan Kadar Protein Ransumnya - Tantan R Wiradarya (Jurnal Ilmu Pertanian Indonesia, 1991)
Using 20 male lambs and 20 male kids of the local breed (about 4 to 5 months old, weighing about 8-10 kg), an experiment was conducted to study the respons of the sheep or goat to the grass-concentrate ration. The grass protein content was about 2 % and its gross energy content was about 4300 cal/gram dry matter. Three batches of concentrates was formulated to contain protein of 20, 30 and 40 % for lambs and 10, 20, and 30 % for kids (as fed basis) while their energy contents were maintained at about 3800 cal/gram dry matter. Two animals of each species were slaughtered at the beginning of the experiment to examine the initial carcass composition. The duration of the experiment was 4 months. The results indicated that as the protein of the ration increased, the daily protein consumption of both sheep (153 to 259 grams per animal) and goat (65 to 119 grams per animal), the price of ration per kg of body weight gain ($ 1.4 to $ 2.5) increased and the income over feed cost (1.2 to 0.7) decreased (P < 0.05). But its effect on the meat production performances of the animals were not significant.